JUADAH DI KANAGARIAN BALAH AIE KECAMATAN VII KOTO SUNGAI SARIAK KABUPATEN PADANG PARIAMAN - A’yuni, Qurrata; Elida, Elida; Fridayati, Lucy; Siregar, Juliana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This study aims to describe the process of making Juadah in Kanagarian Balah Aie, VII Koto Sungai Sariak District, Padang Pariaman Regency, and to examine the challenges in preserving this tradition. Juadah is a ceremonial offering in the manjalang mintuo procession, which holds symbolic value in Minangkabau culture. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation of two traditional Juadah production businesses.The findings reveal that the Juadah production process still adheres to traditional techniques, requiring approximately 24 hours and involving 4–8 workers. The main challenges faced are the availability of raw materials and price fluctuations, which impact production. Therefore, efforts in education and the involvement of younger generations are essential to preserving the tradition of Juadah making as part of Minangkabau cultural heritage.Keywords: Juadah, Manjalang Mintuo, Tradition Minangkabau, Kanagarian Balah Aie.